Multi-level assessment of chronic toxicity of estuarine sediments with the amphipod Gammarus locusta: I. Biochemical endpoints - Neuparth, Teresa (2005)
União Europeia (UE). Fundo Europeu de Desenvolvimento Regional (FEDER), Fundação para a Ciência e a Tecnologia (FCT) – Programa Operacional “Ciência, Tecnologia, Inovação” (POCTI) - POCTI/BSE/41967/2001, fellowships BD/21613/99, BD/11022/97, BD/11575/97, BPD/11588/02.